2010
DOI: 10.1038/nature09159
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of parkinsonian motor behaviours by optogenetic control of basal ganglia circuitry

Abstract: Neural circuits of the basal ganglia are critical for motor planning and action selection1-3. Two parallel basal ganglia pathways have been described4, which are proposed to exert opposing influences on motor function5-7. According to this classical model, activation of the direct pathway facilitates movement and activation of the indirect pathway inhibits movement. However, more recent anatomical and functional evidence has called into question the validity of this hypothesis8-10. Because this model has never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

142
1,597
16
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,645 publications
(1,762 citation statements)
references
References 28 publications
142
1,597
16
7
Order By: Relevance
“…The number of cFos-positive dentate granule neurons, which reflects neuronal activation [15,19], was also significantly higher on the illuminated side of the dentate gyrus compared to the contralateral, non-illuminated dentate gyrus (P,0.05) (Figs. 3A-C).…”
Section: In Vitro and In Vivo Light-elicited Inhibition Of Hilar Gabamentioning
confidence: 93%
See 2 more Smart Citations
“…The number of cFos-positive dentate granule neurons, which reflects neuronal activation [15,19], was also significantly higher on the illuminated side of the dentate gyrus compared to the contralateral, non-illuminated dentate gyrus (P,0.05) (Figs. 3A-C).…”
Section: In Vitro and In Vivo Light-elicited Inhibition Of Hilar Gabamentioning
confidence: 93%
“…Slices were subsequently transferred to a holding chamber containing artificial cerebrospinal fluid (ACSF) containing (in mM) 125 NaCl, 26 NaHCO 3 , 1.25 NaH 2 PO 4 .H 2 O, 2.5 KCl, 1 MgCl, 2 CaCl, and 12.5 glucose at 33uC for 30 min. After resting for 1-5 h at room temperature, experiments were performed on slices perfused with ACSF, warmed to 31-33uC [15].…”
Section: Slice Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that photoactivation of the indirect pathway results in a Parkinsonian state while optical stimulation of the direct pathway totally reverses the appearance of PD, a possible strategy for treatment [32] . Since dopamine (DA) deficiency is responsible for PD, attempts to control DA release were made in 2010.…”
Section: Surprisingly Kravitz Et Al Specifically Expressed Chr2 Inmentioning
confidence: 99%
“…Although optogenetics is applied to control the activity of targeted neurons or to investigate neuronal circuits in the brain, its value in the treatment of diseases due to neuronal degeneration also cannot be ignored, since initial efforts have paid off [32,80] . These promising methods provide new directions to reverse neuronal degeneration.…”
Section: Future Directionsmentioning
confidence: 99%